User Acceptance of Micro-Blogging in the Enterprise - Zhang, Jun; Qu, Yan; Hansen, Derek (Proceedings of the International AAAI Conference on Web and Social Media, 2010)
In this paper, following the IT acceptance theory framework, we analyze factors that affect users’ acceptance of micro-blogging in a large corporate environment. We categorized users into 4 groups based on their posting and reading behaviors: Actives, Dabblers, Lurkers and Skeptics. Groups show different perceived benefits, cost concerns, and social influence factors. The work can help both practitioners and scholars build an initial understanding of user acceptance of micro-blogging in the Enterprise.